The Diversity Of Anura Order At Lake Gegas Of Musi Rawas Regency, South Sumatera Province - Harmoko, Harmoko; Samitra, Dian; Sepriyaningsih, Sepriyaningsih; Yustian, Indra; Setiawan, Arum (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2020)
The purpose of this study was to analyze the diversity of the Anura order in Lake Gegas of Musi Rawas Regency, South Sumatra Province. The research method employed was the cruising method. The cruise was done in every part of Lake Gegas to record the Anura species. Based on the results of the study, 7 species of Anura were found consisting of 5 families and 6 genera. The most commonly found species was the Fejervarya cancrivora. One species found in the IUCN’s Near Threatened (NT) category was the Limnonectes paramacrodon. Based on the results of the study, it can be concluded that the Anura order in Lake Gegas of Musi Rawas Regency, South Sumatra Province was in the moderate diversity category. It was also found a species in the near-threatened category called Limnonectes paramacrodon. Keanekaragaman Ordo Anura di Danau Gegas Kabupaten Musi Rawas Provinsi Sumatera Selatan Abstrak: Tujuan dari penelitian ini adalah untuk menganalisis keanekaragaman ordo Anura di Danau Gegas Kabupaten Musi Rawas Provinsi Sumatera Selatan. Metode penelitian yang digunakan yaitu dengan metode jelajah. Jelajah dilakukan di setiap bagian Danau Gegas untuk mendata spesies ordo Anura. Berdasarkan hasil penelitian, ditemukan 7 spesies ordo Anura yang terdiri dari 5 famili dan 6 genus. Individu paling banyak ditemukan adalah Fejervarya cancrivora. Ditemukan 1 spesies yang dalam IUCN kategori Near Threatened (NT) atau “hampir terancam”yaitu Limnonectes paramacrodon. Berdasarkan hasil penelitian dapat disimpulkan bahwa: keanekaragaman ordo Anura di Danau Gegas Kabupaten Musi Rawas Provinsi Sumatera Selatan dalam kategori keanekaragaman sedang. Dan ditemukan spesies dalam kategori hampir terancam yaitu Limnonectes paramacrodon.